الدَّولة المـَدَنِيَّة بين الدَّولة في صَدْرِ الإِسلام والدَّولة القانونيّة الحديثة "دراسة مقارنة" - يحي عبد محجوب أحمد الحمد; Yahya Abed Mahgoob 'Ahmad Al-Hamid (Universiti Sains Islam Malaysia, 2024)
Matric: 3171287 (FSU)